ANALISIS PENGARUH SUKU BUNGA DAN PRODUK DOMESTIK BRUTO TERHADAP PERMINTAAN KREDIT PEMILIKAN RUMAH PADA BANK TABUNGAN NEGARA DI INDONESIA TAHUN 2001-2014 - Desri H Siagian; Rosyetti '; Darmayuda ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted in Indonesia to examine how the effect of interest rate and the Gross Domestic Product of the Home Loan Demand in the State Savings Bank Year period 2001-2014. Interest Rates and the Gross Domestic Product as independent variables while housing loans as the dependent variable. The data used in this research is secondary data in the form of time series from 2001 through 2014, sourced from the Annual Report Publication of the State Savings Bank (BTN) and the Central Statistics Agency (BPS). This study uses secondary data were analyzed using multiple linear regression analysis, using the computer program SPSS version 17.0. In this study performed classical assumption, statistical tests (t-test and F-test), partial correlation coefficient test and correlation of multiple determination. The results showed that simultaneously (together) independent variables have an effect on the dependent variable with a probability of 0.000. Partially, variable gross domestic product have a significant effect compared with a variable interest rate. The predictive ability of these two variables to the demand of housing loans was 98.50% (R2 = 0.9850), as indicated by the adjusted R2, while the remaining 1:50% influenced by other factors not included in the study variables.Keywords : Interest Rate, the Gross Domestic Product and Housing Credit.